Islamic Law Challenges in Addressing Human Trafficking and Sexual Exploitation - Nur Insani; Karimullah, Suud Sarim; Sulastri (Jurnal Hukum Islam, 2023)
Human trafficking and sexual exploitation remain complex global problems. Islamic law, as one of the legal systems in the world, has a strategic role in participating in overcoming this problem. However, the Islamic legal norms implementation requires support from the state and society. This research discusses the strategic role and challenges of the law in overcoming human trafficking and sexual exploitation. The research method used normative Islamic law with a philosophical approach. The analysis technique used prescriptive analysis, with the analysis process using Islamic legal reasoning. The research results show that Islamic law has a strategic role in resolving the problem of human trafficking and sexual exploitation. The argument is that, philosophically, Islamic law emphasizes the importance of maintaining human honor and dignity, while theoretically, Islamic law recognizes two main concepts in punishment, namely hudud and ta'zir. Hudud is a punishment determined by Allah and has clear rules in the Quran and Hadith. Meanwhile, ta'zir is a punishment determined by a judge for the benefit of society. The challenges of Islamic law in overcoming human trafficking and sexual exploitation are a lack of understanding of Islamic legal norms, which requires human values and justice; Islamic law is not implementable; and there is a perception that the principles of Islamic law can only be applied in Islamic countries. Therefore, global Muslim countries and communities are the main actors in maximizing the application of Islamic legal principles in overcoming human trafficking and sexual exploitation.